Answer:
[tex]{(3 {n}^{3}) }^{2} = 9 \times n \times n \times n \times n \times n \times n.[/tex]
Step-by-step explanation:
The given expresion is
[tex] {(3 {n}^{3}) }^{2} [/tex]
We want to rewrite this expression without exponents.
We use the property of exponents given as
[tex] ({ {a}^{n} })^{m} = {a}^{mn} [/tex]
We apply this property to get:
[tex] {(3 {n}^{3}) }^{2} = {3}^{2} \times {n}^{2 \times 3} [/tex]
This gives us
[tex] {(3 {n}^{3}) }^{2} = 9 {n}^{6} [/tex]
[tex] {(3 {n}^{3}) }^{2} = 9 \times n \times n \times n \times n \times n \times n[/tex]